Uma análise do crescimento econômico na faixa de fronteira: o caso do Paraná - Rocha, Alberto Alves da (2013)
The aim of this study was to analyze the evolution of the development of the 139 municipalities that are in the strip of border of Paraná, through analysis of Index FIRJAN Municipal Development Index (IFDM) and the three categories that compose it: IFDM Education, IFDM Employment and Income IFDM health, in the period 2000-2010. For this research, the literature review included the study of the main theories of regional economics for studies of regional development that explains the spatial distribution of development detected in the studies in question. Survey data were obtained from the IBGE, the Federation of Industries of Rio de Janeiro - FIRJAN, Ipardes and Ministry of National Integration. The data were processed and analyzed from the viewpoint of statistical and GIS in the spatial distribution of the results. The results allowed us to analyze and understand the formations of type (clusters) space, positive and negative, in the grouping of the values assigned by IFDM to municipalities under study. Also, you can see the formation of anomalies (outliers) where some municipalities have different values than their neighbors. Results are shown in graphs and maps thematic, produced using software for statistical analyzes that allow the spatial distribution of data to a visual analysis of the final results.